Language Situation and Language Legislation of Ukraine in the Context of Experience of the Countries with Similar Historical Background - KOBELIANSKA, Oksana I.; KOMARNYTSKA, Tamara K.; KUZMENKO, Yuliia S.; MAZUR, Svitlana M.; FILONOVA, Viktoriia O. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The paper highlights the peculiarities of language legislation in Ukraine as compared to the corresponding laws of some other countries that have experienced similar language problems concerning the abuse of the national language and forcing the language of the invader. Special attention has been paid to the description of the language laws of Latvia, Lithuania and Republic of Korea as compared to the newly adopted language law of Ukraine. The text of the laws on the languages of Latvia, Lithuania, Republic of Korea and Ukraine were the material of the study. As a supporting material, the texts of the constitutions of Latvia, Ukraine, Moldova, as well as Basic Law: Israel – The Nation-State of the Jewish People, the language law of France, the European Charter for Regional Languages, were used. Many common features have been observed in language legislation of the above-mentioned countries. However, Ukraine seems to have a number of problems concerning implementation of the legislative decisions related to financial issues as well as sporadic character of legal procedures which leads to lack of real legislative mechanisms of language conflict regulation and state control of language legislation implementation.